Peran Psikologi Manajemen dalam Optimalisasi Pengambilan Keputusan Organisasi : Studi Literatur Review - Alfan Fadli; Hosniyatul Hasanah; Kamalia Amaniyah; Mu’allimin Mu’allimin (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze the relationship between decision making and management psychology, especially in the context of organizations and education. The research method used is a systematic literature study with a qualitative approach, collecting and analyzing data from sources such as books, journals, and previous research. The results of the study indicate that optimal decision making is influenced by the leader's ability to manage emotions, adaptive leadership style, and understanding of the psychological dynamics of individuals and groups. In the context of education, the integration of management psychology through the application of motivational principles, psychological test-based selection, and curriculum development has been shown to increase the effectiveness of decision making. The discussion underlines the importance of a holistic approach that combines technical aspects of management with psychological understanding to create an efficient and results-oriented organizational and educational environment.